Cannabinoid receptor antagonist SR141716A decreases operant ethanol self administration in rats exposed to ethanol-vapor chambers. - Rodriguez de Fonseca Fernando; Roberts Amanda J; Bilbao Ainhoa; Koob George F; Navarro Miguel (Acta Pharmacologica Sinica, 2016)
AIM: To study the potential role of dependence status on CB1-mediated blockade of ethanol self-administration. METHODS: We examined the effects of the cannabinoid antagonist SR141716A (0, 0.03, 0.3, and 3 mg/kg) on operant ethanol (10% v/v) self-administration in male Wistar rats that were made ethanol-dependent by chronic (14 d) exposure to ethanol vapor-chambers or exposed to air in identical vapor chambers. RESULTS: Dependent animals responded more for ethanol than did air control nondependent rats. The acute administration of a 3 mg/kg dose of SR141716A almost suppressed ethanol self-administration only in ethanol dependent animals. However, operant responses for food were not affected by the administration of SR141716A. CONCLUSION: These results further support that cannabinoid CB1 receptor blockade may have a potential utility for the treatment of alcoholism.